Analisis Manajemen Konten Dalam Proses Produksi Akun Instagram @Daihatsuofficialclub di Pt Astra Daihatsu Motor - Puan Dhana Mulyawan; David Rizar Nugroho; Ika Yuliasari (Jurnal Riset Rumpun Seni, Desain dan Media, 2026)
This research is grounded in the growing use of social media as a digital communication tool for companies to strengthen engagement with their audiences, including user communities. The study aims to explain the content management practices of the Instagram account @daihatsuofficialclub, which is managed by the Marketing Support team of PT Astra Daihatsu Motor (ADM). The research focuses on how content is planned, managed, and utilized as part of ADM’s digital communication strategy to build stronger connections with 21 official Daihatsu user communities. A descriptive qualitative method was employed through internship-based observation and interviews with the account management team. The findings show that the content management process applies the AIDA model through visually appealing posts, relevant information, community-centered storytelling, and interactive calls-to-action that encourage member participation. The implementation of the SOME model further supports a structured workflow across the stages of Share, Optimize, Manage, and Engage. Content marketing analysis indicates that the content fulfills key indicators of relevance, accuracy, value, readability, discoverability, and consistency. These results highlight that the management of @daihatsuofficialclub operates effectively, reflects a human-centered communication approach, and aligns with ADM’s digital communication strategy, contributing to stronger engagement, community closeness, and user loyalty.